0276 The role of various predictors of seizure recurrence in assignment of young men to professions with associated exposure to (seizure) risk factors. (23rd June 2014) - Tavor, Michal; Neufeld, Miri Y; Chodick, Gabriel; Zack, Oren; Moshe, Shlomo
Abstract : Objectives: To study the risk of epileptic seizures as a function of disease severity and occupational stress (physical and mental) in new military recruits in the Israel Defense Forces (IDF). Method: The medical records of over 145 000 18-year old men, recruited to the IDF between the late-nineties and early two-thousands, were used to assemble a cohort, which was followed for a period of 36 months. The severity of the disease was determined according to 5 categories. Recruits were subdivided according to the following occupational categories: Combat Units (CU), Maintenance Units (MU) and Administrative Units (AU). Results: The annual incidence rate for a first seizure was 26/100 000. The rates in CU and MU were lower than AU (0.41 and 0.81 vs. 1 respectively, p < 0.01). Similar findings were found in other disease categories. Conclusions: The low rate for a first seizure and the lower overall seizure rate in CU compared to MU and AU may be explained by the recruiting of a healthy population, higher motivation than before, and meticulous adherence to diagnostic criteria. The higher recurrence rate in our research as compared to the previous follow up, may be attributable to the modification of disease categories. Our findings suggest moderating occupational restrictions for epilepsy patients and using EEG and relapse-free periods of 2–6 years as fitness for work criteria. We propose the reassessment of severity criteria currently used by the IDF.